(untitled) (American Journal of Islam and Society, 1999)
This article explores Ibn Khaldun’s theories and ideas about the causes that lead to the rise and decline of civilizations. By emphasizing the dynamic and interdisciplinary character of Ibn Khaldun’s methodology, it systematically shows how moral, social, political, economic, geographical, and cultural factors find their appropriate place in Ibn Khaldun’s schemata. Unlike other studies of Ibn Khaldun’s contributions, this article recasts his ideas in contemporary terminology and at once making Ibn Khaldun’s analysis and prescriptions relevant. The article also examines the central role of welfare, justice, and development in statecraft, and provides a lucid model of a contemporary Islamic welfare state whose muqusid include the material and moral well-being of its citizens.